Capacity Building Needs of Farmers in Duck Rearing and Marketing for Sustainable Food Security in Benue State, Nigeria - Agbo, Dr T. O. O.; D.T, Nongugwa (International Journal of Scientific Research and Management (IJSRM), 2018)
This study identified capacity building needs of farmers in rearing and marketing of duck in Benue State, for sustainable food security. The study was carried out in Benue state. Three research questions and three hypotheses guided the study. Questionnaire survey research design was used for the study. A population of 96 respondents was studied. A 36-item structuredDuck Rearing Capacity Building Needs Questionnaire (DRCBNQ) was used for data collection. The instrument was validated by three experts. Cronbach Alpha reliability method was used to determine the internal consistency of the instrument and a coefficient of 0.81 was obtained. 96 copies of the questionnaire were administered but only 95 were retrieved and data collected were analyzed using mean Improvement Need-Performance Index (INPI). It was found out that poultry farmers needed capacity building in all the 9 items on feeding of duck, needed capacity building in all the 11 items on management of duck and needed capacity building in all the 16 items on marketing of duck. It was therefore recommended that Agricultural extension agents should utilize the findings of this study on the capacity building needs of farmers to organize training and re-training programmes for improvement of capacity  of poultry farmers in the entire production operations of duck. Farmers could be motivated to attend training and re-training programmes organized for their capacity building in duck production to be effective and efficient in duck production to meet the demand for duck in Benue State